2023
DOI: 10.48550/arxiv.2303.11220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smartphones with UWB: Evaluating the Accuracy and Reliability of UWB Ranging

Abstract: More and more consumer devices implement the IEEE Ultra-Wide Band (UWB) standard to perform distance measurements for sensitive tasks such as keyless entry and startup of modern cars, to find lost items using coin-sized trackers, and for smart payments. While UWB promises the ability to perform time-of-flight centimeter-accurate distance measurements between two devices, the accuracy and reliability of the implementation in up-to-date consumer devices have not been evaluated so far. In this paper, we present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As shown in [19], [20], the DW3x20 devices achieve an accuracy of 5 • for AoA and below 5 cm at a power consumption of 55 mW. [21], [22] characterized the NXP SR040 and SR150 and found its accuracy to be below 8 • or 15 cm. An evaluation of Flueratoru et al [8] showed that the 3DB ACCESS 3DB6830C, the predecessor of the MICROCHIP ATA8352, achieved a similar ranging accuracy of up to 5 cm in line-of-sight (LOS) conditions.…”
Section: Related Workmentioning
confidence: 82%
See 1 more Smart Citation
“…As shown in [19], [20], the DW3x20 devices achieve an accuracy of 5 • for AoA and below 5 cm at a power consumption of 55 mW. [21], [22] characterized the NXP SR040 and SR150 and found its accuracy to be below 8 • or 15 cm. An evaluation of Flueratoru et al [8] showed that the 3DB ACCESS 3DB6830C, the predecessor of the MICROCHIP ATA8352, achieved a similar ranging accuracy of up to 5 cm in line-of-sight (LOS) conditions.…”
Section: Related Workmentioning
confidence: 82%
“…In [13] nRF5x BLE [15]- [18] Qorvo DW3220 [19], [20], [23] NXP SR040, SR150 [21], [22], [24] Microchip ATA8352 [8], [25], [26] Spark SR1000 [27], [28] Frequency ATA8352). As shown in [19], [20], the DW3x20 devices achieve an accuracy of 5 • for AoA and below 5 cm at a power consumption of 55 mW.…”
Section: Related Workmentioning
confidence: 99%
“…A recent study was conducted to evaluate UWB smartphones from major manufacturers, such as Samsung, Apple, and Google [9]. The research found that the tested devices could measure distances with an error of under 20 cm.…”
Section: Literature Reviewmentioning
confidence: 99%